Analysis of the Need for Mathematics Student Worksheets Oriented Towards Discovery Learning to Enhance Critical Thinking Abilities - Fitriyani Fitriyani; Nurhanurawati Nurhanurawati; Ryzal Perdana (Budapest International Research and Critics University, 2023)
Critical thinking ability is a 21st-century learning skill that students must possess. Students with low critical thinking skills will encounter difficulties in problem-solving. The critical thinking skills of students are still lacking due to the use of inadequate teaching materials that do not meet the students' needs. This research aims to analyze the need for student worksheets (LKPD) oriented towards the Discovery Learning model to enhance students' critical thinking skills. This research is of a qualitative analysis type. The study was conducted at MIN 2 West Lampung. The subjects of this research were 1 teacher and 25 students in Grade VA. Data collection was conducted through observation and interviews. The activities carried out during the observation phase involved observing teaching and learning activities, analyzing lesson plans (RPP), and analyzing the learning resources used in the classroom. During the interview phase, the research results indicate that both teachers and students require student worksheets (LKPD) oriented towards discovery learning that can enhance critical thinking skills.